2005
DOI: 10.1080/02640410400021633
|View full text |Cite
|
Sign up to set email alerts
|

Disconnects between popular discourse and home advantage research: What can fans and media tell us about the home advantage phenomenon?

Abstract: Many of the factors identified as influencing the home advantage have an underlying social basis, presumably through the influence exerted by the home crowd. Beliefs in the home advantage and the causes of that advantage also have a social basis: sports coverage and fan discourse focus on some aspects of the phenomenon at the expense of others. This paper compares home advantage research with the use of the concept in media narratives and fan Intemet postings. While there are many similarities across sources, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 35 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…They speculated that females might perceive their home venue more as a public place and less as a home territory to be protected. Smith (2005) noted that home advantage was seldom mentioned in popular discussion of women's teams. He then suggested that the protection of home territory, arousal from crowd noise and increased self-confidence at home were not usually seen as feminine qualities.…”
Section: Introductionmentioning
confidence: 99%
“…They speculated that females might perceive their home venue more as a public place and less as a home territory to be protected. Smith (2005) noted that home advantage was seldom mentioned in popular discussion of women's teams. He then suggested that the protection of home territory, arousal from crowd noise and increased self-confidence at home were not usually seen as feminine qualities.…”
Section: Introductionmentioning
confidence: 99%
“…3,7 Regarding the social bonding and teamcommunity relationship in sport, Smith asserted that fans were less likely to see a women's team as being representative of the local community than a men's team. 29 Consequently, in the HA context, we can expect to see less crowd support for women's matches and less hostility toward women's opponents and referees. Pollard et al demonstrated that, of 193 domestic sports leagues worldwide with average attendances of over 1,500 per match in 2015, only three were women's leagues.…”
Section: The Influence Of Social-cultural Factors In Women's Sportmentioning
confidence: 99%
“…Social support theory (Leifer, 1995; Mizruchi, 1985) and written theory (Ward, 1998), both provide sociological theories on how crowds may have an impact on the outcome of a competition. Crowds can motivate athletes to overachieve, create a supportive social environment for teams and players, or symbolically foster a sense of ritual that provides an advantage to the home team (Smith, 2005). In addition, Pollard (1986), who has been working on the issue of HA in sporting competitions for years, also argues that “football HA is greatest in leagues and tournaments with large spectator numbers”.…”
Section: Crowd Size and Home Field Advantagementioning
confidence: 99%